2019
DOI: 10.2147/ijn.s205095
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hexagonal Boron Nitrides (White Graphene): A Promising Method for Cancer Drug Delivery</p>

Abstract: Advances in low-dimensions nanomaterials drug-carrier have rapidly translated into clinical practice. Interestingly, the two-dimensional (2D) nanomaterials of hexagonal boron nitride (h-BN), so-called “white graphite” are relatively less explored compared to the post popular 2D graphene oxide (GO). However, the unique properties of h-BN nanomaterials make them well suited for the delivery of chemotherapeutic in cancer treatment. Recent studies have shown that the h-BN is a potential candidate in biomedical sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 35 publications
(53 reference statements)
0
52
0
Order By: Relevance
“…All mice had the same incision depth (2 mm) and were administered a bare PP film or drug-loaded PP film with 5 min remote heating at 45 °C in these experiments. However, it is difficult to determine the local concentration of residual released drugs in tissue or blood, as it is not the desired goal of local applied medicine to be available in systemic blood circulation [ 32 , 33 ]. To investigate the physiological consequences of local treatments of PP film on mouse skin, we observed body weight changes following treatment ( Figure 4 b) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…All mice had the same incision depth (2 mm) and were administered a bare PP film or drug-loaded PP film with 5 min remote heating at 45 °C in these experiments. However, it is difficult to determine the local concentration of residual released drugs in tissue or blood, as it is not the desired goal of local applied medicine to be available in systemic blood circulation [ 32 , 33 ]. To investigate the physiological consequences of local treatments of PP film on mouse skin, we observed body weight changes following treatment ( Figure 4 b) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, photothermal-dependent light-responsive CPDs could be employed in temperature-controlled drug delivery and photothermal chemotherapy [61,62]. In this arena, the inorganic metal oxide nanoparticles and fully carbonized graphene The remarkable optical properties of CPDs and cross-linked polymeric properties have inspired potential applications in biomedical sciences [53,54].…”
Section: Biomedical and Theranostic Applications Of Carbon Polymer Dots (Cpds)mentioning
confidence: 99%
“…At the same time, photothermal-dependent light-responsive CPDs could be employed in temperature-controlled drug delivery and photothermal chemotherapy [61,62]. In this arena, the inorganic metal oxide nanoparticles and fully carbonized graphene oxide, CDs, and carbon nanotubes are well-recognized materials; however, CPDs did get much recognition in the research community [63][64][65][66][67][68].…”
Section: Biomedical and Theranostic Applications Of Carbon Polymer Dots (Cpds)mentioning
confidence: 99%
“…The biocompatibility of 2D materials is not only dependent on the surface properties of these materials, such as the functionalization degree and reactive surface, but also the concentration, purity, size, shape, thickness and form of 2D materials. [229][230][231] For example, a study performed by Mateti et al 232 showed that micrometersized h-BN nanosheets possess in vitro biocompatibility against Osteoblast-like cells; however, nanosheets with a lateral size less than 1 μm and a thickness below 100 nm were less biocompatible. It was suggested that this observation may be due to the unsaturated B atoms located at the nanosheet edges or on the surface of the material (in the case of defects) are present in a radical state, triggering faster reactivity kinetics with other active atoms, such as oxygen, to generate ROS and leading to cell death.…”
Section: Biocompatibility and Biodegradabilitymentioning
confidence: 99%